ISLAM DAN ILMU PENGETAHUAN : REKOGNISI PENDIDIKAN ISLAM DI BARAT ABAD KLASIK - Hermawansyah, Hermawansyah; Rama, Bahaking; Yahdi, Muhammad (Prodi PAI STIT Sunan Giri Bima, 2024)
The development of education in the world is inseparable from the contributions of Islam, which has played a significant role in it. Consequently, Islam holds a legitimate position in terms of the quality of education, which should be acknowledged publicly as a marker that these contributions must be academically recognized. The contributions of Islamic education to the world can be seen from the scientific heritage of the medieval period when Europe and the Middle East were engaged in debates over reason. The presence of Islamic education had an impact on the process of classifying knowledge into rational ('aqliah) and transmitted ('naqliah) sciences. This classification led to the emergence of branches of rational sciences, including medicine, mathematics, sciences (physics, astronomy, and chemistry), and sosial sciences (economics, geography, and psychology). In the field of medicine, Abdullah Al-Hasan Bin Al Bin Sina, commonly known as Ibn Sina, emerged with his book